Atomic‐Scale Friction of Black Phosphorus: Effect of Thickness and Anisotropic Behavior. Issue 23 (13th October 2017) - Cui, Ziyi; Xie, Guoxin; He, Feng; Wang, Weiqi; Guo, Dan; Wang, Wei
Abstract: The understanding on the friction properties of black phosphorus (BP) is very crucial for such applications as strain‐engineered devices and micro/nanoelectromechanical systems. Herein, the relationship between the layer number of few‐layer BP flakes and its nanoscale friction, as well as the atomic‐scale friction anisotropy, is studied. BP flakes thicker than about five layers show almost the same friction as that of the bulk value, and the friction increases with the layer number decreasing from five, due to the strengthening mechanism. Obvious friction anisotropy of BP flakes are observed in that the friction for the armchair direction is the highest, that for the zigzag direction the lowest, and that for the lattice orientation between the two directions the intermediate. Supported by the theoretical prediction with 2D Tomlinson model, the observed phenomena are explained by the anisotropies in the amplitudes of the tip‐induced flexural deformations of BP flakes. Abstract : Black phosphorus (BP) flakes thicker than five layers show almost the same friction as that of the bulk, and the friction increases with the layer number decreasing from five. The largest friction of BP is along armchair direction, the smallest along zigzag direction. The friction anisotropy could be greatly reduced with the increase of applied load.